Pericardial Tamponade: An Uncommon Clinical Presentation in cANCA Related Vasculitis and Glomerulonephritis in Association with Very High Titres of ANA - Amaresh Vanga; Amna Z. Rana; Jolanta Kowalewska; Harlan Rust (Case Reports in Nephrology)
ANCA (anti-neutrophil cytoplasmic antibody) vasculitides are systemic autoimmune diseases in which anti-neutrophilic cytoplasmic antibodies activate primed neutrophils, thereby generating an inflammatory cascade resulting in the damage of small sized blood vessels in various organs of the body, including the heart. Pleuropericardial involvement is underrecognized as a complication of ANCA vasculitis and is highlighted in this case report of a 51-year-old male who presented with an initial symptomatic presentation of pleuropericardial effusion progressing to pericardial tamponade in the setting of a later renal biopsy proven pauci-immune crescentic glomerulonephritis with high ANA titres along with positive cANCA (cytoplasmic ANCA) and PR3 (proteinase 3) antibodies. He was found to have acute renal failure which progressively got better with cyclophosphamide.